2013
DOI: 10.1136/gutjnl-2013-305062
|View full text |Cite
|
Sign up to set email alerts
|

Newly diagnosed diabetes mellitus after acute pancreatitis: a systematic review and meta-analysis

Abstract: Patients with AP often develop prediabetes and/or DM after discharge from hospital, and have a greater than twofold increased risk of DM over 5 years. Further studies are warranted to determine the optimal strategy for its detection and whether the risk of developing DM after AP can be reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
277
3
14

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 328 publications
(313 citation statements)
references
References 73 publications
19
277
3
14
Order By: Relevance
“…A higher HR of development of diabetes was found in the present study for patients admitted with AP (HR, 2.15; 95% CI 1.92-2.41). This finding, which is in agreement with those of other studies, 11,12,14 was confirmed by the observation that the ''diabetes'' diagnosed in these AP patients was not attributable to a transient hyperglycemia but rather to a persistent disease. In patients with severe as compared to mild AP, a slightly but not significantly increased HR of diabetes was observed (2.22; 95% CI, 1.50-3.29).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A higher HR of development of diabetes was found in the present study for patients admitted with AP (HR, 2.15; 95% CI 1.92-2.41). This finding, which is in agreement with those of other studies, 11,12,14 was confirmed by the observation that the ''diabetes'' diagnosed in these AP patients was not attributable to a transient hyperglycemia but rather to a persistent disease. In patients with severe as compared to mild AP, a slightly but not significantly increased HR of diabetes was observed (2.22; 95% CI, 1.50-3.29).…”
Section: Discussionsupporting
confidence: 92%
“…13 Authors of a recently published meta-analysis concluded that patients treated for AP may be at higher risk of developing diabetes after discharge; however, the severity of AP had a minimal effect on the studied outcomes in this analysis. 14 To the knowledge of the authors of this report, no study investigating the bidirectional relationship between AP and diabetes has been performed with the same population and with the same source of data. Furthermore, the effects of disease severity on this relationship have not been fully evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic diseases such as pancreatitis and pancreatic cancer often cause hyperglycemia, referred to as pancreatic or pancreatogenic diabetes [55][56][57][58][59]. The mechanisms by which pancreatitis and pancreatic cancer promote hyperglycemia remain to be fully clarified, but insulin secretion is often impaired in these patients [60].…”
Section: Beta-cell Area and Function In Pancreatic Diseasesmentioning
confidence: 99%
“…While its statistics were, until recently, largely confined to chronic pancreatitis and pancreatic cancer (3,4), emerging large scale population-based studies show that more than 60% of all cases of diabetes of the exocrine pancreas are due to new-onset diabetes after acute pancreatitis (NODAP) (5)(6)(7), and that the risk of NODAP may not depend on severity of acute pancreatitis (8,9). However, the molecular mechanisms underlying the pathophysiology of NODAP remain unclear.…”
Section: Introductionmentioning
confidence: 99%